“DOCTOR HONORIS CAUSA” – WOLFGANG MIEDER - Fortsakis, Theodore; Alexiadis, Minas Al.; Kaplanoglou, Marianthi; Doulaveras, Aristedes N.; Mieder, Wolfgang (Proverbium - Yearbook, 2015)
On December 16, 2014, Professor Wolfgang Mieder from the University of Vermont received the special honor of a “doc-tor honoris causa” from the prestigious University of Athens in Greece. The proclamation festivity took place in the main build-ing of the university at Athens with many administrators, profes-sors, and students in attendance for the special celebration. It was the wish of the colleagues and friends at the University of Ath-ens that the various speeches of the evening would be publishedin Proverbium: Yearbook of International Proverb Scholarshipas a sign of the high regard of not only Prof. Mieder’s contribu-tions to international folkloristics in general and international paremiology in particular but also as a tribute to proverb scholarsthroughout the world. The speeches were delivered in Greek andare presented here in English translation. Prof. Mieder’s address was given in English.